AN OTHER PROOF OF THE INSOLUBILITY OF FERMAT'S CUBIC EQUATION IN EISENSTEIN'S RING - Elias Lampakis (Journal of the Indonesian Mathematical Society, 2013)
pdf abstractDOI : http://dx.doi.org/10.22342/jims.19.1.130.61-66